2017
DOI: 10.1128/mbio.02296-16
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Integron Cassette Excision Dynamics Shape a Trade-Off between Evolvability and Genetic Capacitance

Abstract: Integrons ensure a rapid and “on demand” response to environmental stresses driving bacterial adaptation. They are able to capture, store, and reorder functional gene cassettes due to site-specific recombination catalyzed by their integrase. Integrons can be either sedentary and chromosomally located or mobile when they are associated with transposons and plasmids. They are respectively called sedentary chromosomal integrons (SCIs) and mobile integrons (MIs). MIs are key players in the dissemination of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…Since the integrase recognizes the structure of the bottom strand of attC sites ( 6 ), we based our features on the predicted folding of the bottom strand of each mutant using the RNAfold program from the ViennaRNA 2.1.8 package (Supplementary Materials) ( 24 ). Our list included several global features describing attC site folding, such as Gibbs free energy (∆ G ) of the structures, the probability to fold a functional structure (pfold), i.e., a structure with correctly folded integrase binding sites ( 25 , 26 ), and others. It also included a set of characteristics for each particular base, such as the nucleotide present at that position, its pairing probability, and positional entropy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the integrase recognizes the structure of the bottom strand of attC sites ( 6 ), we based our features on the predicted folding of the bottom strand of each mutant using the RNAfold program from the ViennaRNA 2.1.8 package (Supplementary Materials) ( 24 ). Our list included several global features describing attC site folding, such as Gibbs free energy (∆ G ) of the structures, the probability to fold a functional structure (pfold), i.e., a structure with correctly folded integrase binding sites ( 25 , 26 ), and others. It also included a set of characteristics for each particular base, such as the nucleotide present at that position, its pairing probability, and positional entropy.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have already suggested that attC site recombination frequency depends on numerous properties related to their sequence, structure, and stability ( 6 , 8 , 9 , 11 , 12 , 25 , 26 , 40 , 41 ). Most of these factors apply to both attI × attC and attC × attC recombination reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In attC recombination, replication is not only important for the formation of the folded bs, but also for the resolution of recombination products [32] [33]. However, the presence of single stranded proteins (SSP) hampers the formation of a fully folded attC bs in absence of integron integrase (IntI) [34] [35].…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the number of investigations conducted examining other drivers of antimicrobial resistance (e.g., pharmaceutic compounds and PTEs), there have been relatively minimal studies on the effects of PAH contamination to AMR, and few prediction models exist. However, research has demonstrated that naphthalene and phenanthrene exposure were primarily linked to conjugative transfer of genes mediated by class I integrons (Wang et al 2017); these genetic mechanisms allow bacteria to adapt and evolve rapidly through the acquisition, stockpiling and differential expression of new genes and have been previously correlated with clinical antibiotic resistance (Gillings et al 2008;Deng et al 2015;Loot et al 2017). Genes for PTEs and ARGs have been found in bacterial plasmids and could facilitate the dissemination of these genes under elevated stresses (Li et al 2015a;Zhai et al 2016).…”
Section: Pahs and Amrmentioning
confidence: 99%